2017
DOI: 10.1073/pnas.1618596114
|View full text |Cite
|
Sign up to set email alerts
|

Cas9-mediated genome editing in the methanogenic archaeon Methanosarcina acetivorans

Abstract: Although Cas9-mediated genome editing has proven to be a powerful genetic tool in eukaryotes, its application in Bacteria has been limited because of inefficient targeting or repair; and its application to Archaea has yet to be reported. Here we describe the development of a Cas9-mediated genome-editing tool that allows facile genetic manipulation of the slow-growing methanogenic archaeon Methanosarcina acetivorans. Introduction of both insertions and deletions by homology-directed repair was remarkably effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(135 citation statements)
references
References 46 publications
8
126
0
1
Order By: Relevance
“…The methanol oxidation coupled with AQDS reduction in the presence of BES described here is the first demonstration of a methanogen conserving energy to support growth with electron transfer to an external electron acceptor as the sole means of energy conservation. The ability of M. acetivorans to grow in this manner, and the availability of tools for genetic manipulation (2527) provide the opportunity for functional analysis of extracellular electron transfer in an archaeon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methanol oxidation coupled with AQDS reduction in the presence of BES described here is the first demonstration of a methanogen conserving energy to support growth with electron transfer to an external electron acceptor as the sole means of energy conservation. The ability of M. acetivorans to grow in this manner, and the availability of tools for genetic manipulation (2527) provide the opportunity for functional analysis of extracellular electron transfer in an archaeon.…”
Section: Resultsmentioning
confidence: 99%
“…Tools are available for genetic manipulation of the methanogen Methanosarcina acetivorans (2527). A methyl-coenzyme M reductase from an uncultured ANME was introduced into M. acetivorans to generate a strain that could convert methane to acetate with simultaneous reduction of Fe(III) (28).…”
Section: Introductionmentioning
confidence: 99%
“…To test the hypothesis that MA4545 is responsible for S- methylation of Cys472 in McrA, we deleted the gene in M. acetivorans using recently developed Cas9-based genome editing tools (34). Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) showed that the McrA tryptic peptide containing the Cys residue of interest was 14 Da lighter in the mutant than in the corresponding peptide from wild-type, consistent with loss of a methyl group in the mutant (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…All mutations in M. acetivorans were introduced using a Cas9-based genome editing technique (34). Mutagenic plasmids were derived from pDN201, a base vector containing Cas9 from Streptococcus pyogenes under the control of the tetracycline-inducible pMcrB(tetO1) promoter.…”
Section: Methodsmentioning
confidence: 99%
“…The elucidation of CRISPR-Cas biology has rendered this system convenient for engineering of prokaryotic [67], archaeal [68], and eukaryotic [23] genomes. The simplest and most commonly used implementation of CRISPR-Cas systems consists of only two components: an endonuclease (e.g.…”
Section: Mutagenesis Methods For Genome Engineering and Genome-wide Smentioning
confidence: 99%